Overweight, obesity, and dyslipidemias at a mexican northeastern university population - Magallanes Monrreal, Martha; Gallegos Cabriales, Esther Carlota; Carrillo Cervantes, Ana Laura; Sifuentes Leura, Daniel; Olvera Blanco, María Antonieta (Investigación y Educación en Enfermería, 2010)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– /* Font Definitions */ @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-520092929 1073786111 9 0 415 0; @font-face font-family:NewsGothicBT-Bold; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0; @font-face font-family:NewsGothicBT-Roman; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 134676480 16 0 131073 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US; .MsoPapDefault mso-style-type:export-only; margin-bottom:10.0pt; line-height:115%; @page WordSection1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.WordSection1 page:WordSection1; –><!– [if gte mso 10]> <![endif]–> Objective: to determine the overweight, obesity and dyslipidemias prevalence at a mexican northeastern university population. Methodology: transversal cut descriptive study; stratified randomized sampling was made with proportional assignation of 292 people. Blood samples were taken to determine total cholesterol, low and high density lipoproteins, weight and height were measured to cal culate the body mass index (BMI). Results: a total prevalence of 31,2% overweight was found (45.8% in men and 22.4% in women) and 15.1% of obesity. The hypercholesterolemia global prevalence was of 23.6% (31.4% in men and 18.4% in women) Being higher in manual workers and managers (53.8% and 52.8%, respectively). The people’s BMI above the normal range have 2.55 times the risk of dyslipidemia compared to the ones who have a normal weight (IC95:1.46–4.46). The multivariate analysis showed significant differences for the variables: total cholesterol, high density lipoprotein and triglycerides between the two groups compared; finally the Tuckey Post Hoc analysis showed significant differences in total colesterol and high and low density lipoproteins between normal weight and overweight. Conclusion: there is ahigher prevalence of obesity in men than in women, the association between obesity and total colesterol suggests a bigger cardiovascular disease risk.